Dialektika Pluralise Hukum: Upaya Penyelesaian Masalah Ancaman Keberagaman dan Keberagamaan di Indonesia - Novita Dewi Masyithoh (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2016)
Conflict resolution on SARA requires pluralistic approaches. Hence, the presence of legal pluralism becomes a new approach to resolve the problem. This study is qualitative research that conveys three dimensions of legal pluralism, namely natural law, state law, and society law. The study used secondary data, with primary and secondary legal materials obtained by documentation resources. Data were analyzed inductively, used the contemporary theories to produce more conceptual and general propositions for conclusions and recommendations. The result shows that there have been 8 cases on SARA conflict in Indonesia during the last three years. To solve these problems, religious leaders can use the natural law approach to re-internalize religious values and tolerance. In addition, the government also should understand that those conflicts were a form of society law owing to the discreditable law society and religious diversity. Therefore, a non-penal policy with persuasive appeals is needed to reduce the problems. However, penal policy through law enforcement should also be implemented as a form of state positivism law. In other words, state positivism law should go hand in hand with natural law and society law in order to reach the best decision based on moral and religious ethics as well as social values.